Synaesthesia / Classic and Contemporary Readings - Baron-Cohen Simon; Harrison John E (Blackwell Publishing, 1997)
This volume brings together what is known about this fascinating neurological condition. Foreword, Acknowledgements, Background, Synesthesia: An Introduction, Synesthesia: Phenomenology and Neuropsychology, Classic Papers, Color Association, On Colored-Hearing Synesthesia: Cross Modal Translations of Sensory Dimensions, ''Correspondences'', Neuroscientific Perspectives, Synesthesia: A Review of Psychological Theories, The Physiological Basis of Synesthesia, Perception and Sensory Information in Synesthetic Experience, Synesthesia: Is a Genetic Analysis Feasible?, Developmental Perspectives, Synesthesia: Implications for Modularity of Mind, Neonatal Synesthesia: Implications for the Processing of Speech and Faces, Clinical and Personal Perspectives, Synesthesia: Possible Mechanisms, Two Synathletes Talking Color, Index.